Short-term clinical disease progression in HIV-infected patients receiving combination antiretroviral therapy: results from the TREAT Asia HIV observational database - Srasuebkul, P.; Lim, P.L.; Lee, M.P.; Kumarasamy, N.; Zhou, J.L.; Sirisanthana, T.; Li, P.C.K.; Kamarulzaman, A.; Oka, S.; Phanuphak, P.; Vonthanak, S.; Merati, T.P.; et al. (2009)
Objective. The aim of our study was to develop, on the basis of simple clinical data, predictive short-term risk equations for AIDS or death in Asian patients infected with human immunodeficiency virus (HIV) who were included in the TREAT Asia HIV Observational Database. Methods. Inclusion criteria were highly active antiretroviral therapy initiation and completion of required laboratory tests. Predictors of short-term AIDS or death were assessed using Poisson regression. Three different models were developed: a clinical model, a CD4 cell count model, and a CD4 cell count and HIV RNA level model. We separated patients into low-risk, high-risk, and very high-risk groups according to the key risk factors identified. Results. In the clinical model, patients with severe anemia or a body mass index (BMI; calculated as the weight in kilograms divided by the square of the height in meters) <= 18 were at very high risk, and patients who were aged ! 40 years or were male and had mild anemia were at high risk. In the CD4 cell count model, patients with a CD4 cell count <50 cells/mu L, severe anemia, or a BMI <= 18 were at very high risk, and patients who had a CD4 cell count of 51-200 cells/mu L, were aged ! 40 years, or were male and had mild anemia were at high risk. In the CD4 cell count and HIV RNA level model, patients with a CD4 cell count <50 cells/mu L, a detectable viral load, severe anemia, or a BMI similar to 18 were at very high risk, and patients with a CD4 cell count of 51-200 cells/mu L and mild anemia were at high risk. The incidence of new AIDS or death in the clinical model was 1.3, 4.9, and 15.6 events per 100 person-years in the low-risk, high-risk, and very high-risk groups, respectively. In the CD4 cell count model the respective incidences were 0.9, 2.7, and 16.02 events per 100 person-years; in the CD4 cell count and HIV RNA level model, the respective incidences were 0.8, 1.8, and 6.2 events per 100 person-years. Conclusions. These models are simple enough for widespread use in busy clinics and should allow clinicians to identify patients who are at high risk of AIDS or death in Asia and the Pacific region and in resource-poor settings.